Fourier Transform Infrared Spectroscopy of "Bisphenol A". (24th August 2016) - Ullah, Ramzan; Ahmad, Ishaq; Zheng, Yuxiang
Abstract : FTIR (400–4000 cm −1 ) spectra of "Bisphenol A" are presented. Absorption peaks (400–4000 cm −1 ) are assigned on the basis of Density Functional Theory (DFT) with configuration as B3LYP 6-311G++ (3df 3pd). Calculated absorption peaks are in reasonable reconciliation with experimental absorption peaks after scaling with scale factor of 0.9679 except C-H and O-H stretching vibrations.